Deep Orbital Sub-Q Hyaluronic Acid Filler Injection for Enophthalmic Sighted Eyes in Parry–Romberg Syndrome. Issue 5 (September 2018) - Feldman, Ilan; Sheptulin, Vladimir A.; Grusha, Yaroslav O.; Malhotra, Raman
Abstract : Purpose: The authors present a consecutive series of deep orbital Sub-Q injections to treat enophthalmic sighted eyes in Parry–Romberg syndrome patients. Methods: Retrospective, interventional case series in 2 centers. Data were collected on patient demographics, Parry–Romberg syndrome onset age, previous orbital and eyelid surgeries, diplopia, ocular movement restriction before and after the injection, number of injections, interval between injections, indication for any top-up or dissolution of filler, and any other complications. In all cases, the hyaluronic acid gel used was Restylane Sub-Q + Lidocaine. Results: A total of 8 injections on 3 patients with Parry–Romberg syndrome, and significant enophthalmos is reported. All injections were with deep orbital Sub-Q filler. All patients were females, aged 32, 24, and 52 years old while their symptoms started at 15, 16, and 30 years old, respectively. None had orbital surgery prior to the injection. Follow up period was 2, 7, and 5 years respectively. All presented a significant enophthalmos of 4 mm which reduced to 1 mm after the injection, and duration effect was 18, 24, and 20 months, respectively. We observed a significant improvement in enophthalmos, lagophthalmos, exposure keratopathy, and even ocular motility. Lagophthalmos improved from 1, 4, and 7 mm to 0, 1, and 2 mm post injection. Ocular motility improved with no onset of new limitation or diplopia. Lower eyelid retraction increased in 1 patient after orbital injection. No other complications occurred. Conclusions: Deep orbital Sub-Q hyaluronic injection for treatment of enophthalmos in Parry–Romberg syndrome is an useful option in sighted eyes. Abstract : This is the first report to use deep orbital Sub-Q injection for treatment of enophthalmic sighted eyes with Parry–Romberg syndrome.